Textures and chemical composition of magnetite from iron oxide-copper-gold (IOCG) and Kiruna-type iron oxide-apatite (IOA) deposits and their implications for ore genesis and magnetite classification schemes - Beaudoin, Georges; Xiaowen, Huang (Economic Geology, 2019)
Textural and compositional data of magnetite from Igarapé Bahia, Alemao, Sossego, Salobo, and Candelaria iron oxide copper-gold (IOCG) and El Romeral Kiruna-type iron oxide-apatite (IOA) deposits show that some magnetite grains display oscillatory zoning or have been reequilibrated by oxy-exsolution, coupled dissolution and reprecipitation (CDR) reactions, and/or recrystallization. Textures formed via CDR are most widespread in the studied samples. The original oscillatory zoning was likely derived from the crystal growth during fluctuating fluid compositions rather than from variation in temperature and oxygen fugacity. The oxy-exsolution of ilmenite in magnetite is attributed to increasing oxygen fugacity and decreasing temperature with alteration and mineralization, resulting in product magnetite with lower Ti and higher V contents. Recrystallization of some magnetite grains is commonly due to high-temperature annealing that retained primary compositions. Two different types of CDR processes are defined according to textures and chemical compositions of different generations of magnetite. The first generation of magnetite (Mag-1) is an inclusion-rich and trace element-rich core, which was replaced by an inclusion-poor and trace element-poor rim (Mag-2). The third generation of magnetite (Mag-3), inclusion poor but trace element rich, occurs as veins replacing Mag-2 along fractures or grain margins. Type 1 CDR process transforming Mag-1 to Mag-2 is more extensive and is similar to processes reported in skarn deposits, whereas type 2 CDR process is local, transforming Mag-2 to Mag-3. During type 1 CDR process, minor and trace elements Si, K, Ca, Mg, Al, and Mn in magnetite are excluded, and Fe contents increase to various extents, in contrast to type 2 CDR process, which is characterized by increased contents of Si, K, Ca, Mg, Al, and Mn. Type 1 CDR process is possibly induced by the changing fluid composition and/or decreasing temperature during progressive alteration and ore formation, whereas type 2 CDR ...